2020
DOI: 10.1186/s12886-020-01444-7
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of diabetic macular edema complicated by an atypical macular hole

Abstract: Background: Here we report two patients who developed an atypical macular hole (MH) during the treatment course for diabetic macular edema (DME). Case presentations: Patient 1 was a 73-year-old male. Optical coherence tomography (OCT) revealed perifoveal retinoschisis (RS) in addition to cystoid macular edema and serous retinal detachment (SRD) in his left eye, and that an MH had developed during the clinical course. A convex surface was formed at the MH margin toward the vitreous cavity, and granular shadows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The management of secondary MH after DV has rarely been discussed in the literature. In previous case reports, most patients received primary DV due to non-clearing VH [ 4 , 14 , 31 33 ], which was less complicated than in our cases. Most patients underwent ERM removal with or without ILM peeling as MH repair surgery.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The management of secondary MH after DV has rarely been discussed in the literature. In previous case reports, most patients received primary DV due to non-clearing VH [ 4 , 14 , 31 33 ], which was less complicated than in our cases. Most patients underwent ERM removal with or without ILM peeling as MH repair surgery.…”
Section: Discussionmentioning
confidence: 45%
“…ERM was the most common predisposing factor for secondary MH after DV as reported in the literature [ 4 , 30 , 31 , 35 ]. The tangential traction exerted on the weakened fovea caused subsequent MH formation within 7 months to 5 years [ 4 , 30 , 31 , 35 ]. In the present study, Cases 4–9 (6 eyes) also showed ERM and subsequent MH formation after primary DV.…”
Section: Discussionmentioning
confidence: 99%
“…13 Paradoxically, several case reports have also linked FTMH formation to anti-VEGF injections. Lee and Kim 3 and Yoshida et al 8 reported FTMH formation in a patient with DME after an intravitreal injection of bevacizumab and aflibercept, respectively. Similarly, Muramatsu et al 17 identified FTMH formation following intravitreal injection of ranibizumab in a patient with CME secondary to a branch retinal vein occlusion.…”
Section: Discussionmentioning
confidence: 98%
“…FTMH has been reported as a rare complication of CME secondary to diabetes mellitus, central retinal vein occlusion, and uveitis. 4,8 The mechanisms of formation are likely the result of the tractional forces applied perpendicularly to the inner retinal layers by cystoid intraretinal fluid combined with intrinsic inner retinal layer weakness. [8][9][10] Anterior tractional forces applied by a tightly adherent vitreous is another well-known cause of FTMH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a possible mechanism for the FTMH formation in our case is an increased anterior-posterior traction on the fragile retina with an incomplete PVD caused by the rapid shrinkage of the retina due to resolution of the ME. In fact, there have been two reports of FTMH formation in eyes with persistent diabetic macular edema [ 8 , 9 ], and it was also suggested that vitreous injections in eyes with an incomplete PVD may create focal traction which increased the chance of FTMH formation [ 6 ]. On the other hand, a spontaneous closure of an idiopathic macular hole has been reported to occur with the release of vitreous traction due to a complete PVD.…”
Section: Discussionmentioning
confidence: 99%